First person - Giovanna Lucrecia Gallo and Ayelen Valko (Journal of cell science, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Journal of Cell Science, helping early-career researchers promote themselves alongside their papers. Giovanna Lucrecia Gallo and Ayelen Valko are co-first authors on ‘ A novel fission yeast platform to model N-glycosylation and the bases of congenital disorders of glycosylation type I’, published in JCS. Giovanna conducted the research described in this article while a PhD student in Cecilia D'Alessio's lab at Fundación Instituto Leloir, Buenos Aires, Argentina. She is now a postdoc in the lab of Nora Lopez at Centro de Virologia Humana y Animal, Buenos Aires, Argentina, investigating the biological mechanisms underlying virus-host cell interactions, intracellular viral strategies to survive host immune responses and the control mechanisms displayed by the host. Ayelen conducted the research described in this article while a postdoc in Cecilia D'Alessio's lab. She is now a postdoc in the lab of Sebastian Schuck at Heidelberg University Biochemistry Center, Germany, investigating the underlying mechanisms of micro-ER-phagy, an autophagic process that is essential for elimination of the ER during ER stress.